A case of pemphigus foliaceus and pustular psoriasis A case of pemphigus foliaceus and pustular psoriasis with a brief review of literature - Darjani Abbas; Raﬁ ei Rana; Mesbah Alireza; Shafaei Sareh; Raﬁ ee Behnam (Our Dermatology Online, 2017)
Rarely pemphigus foliaceus could be associated with generalized pustular psoriasis. A 66-year-old woman with diffuse flaccid bullae and erosions of pemphigus foliaceus underwent two sessions of pulse therapy of corticosteroid and oral prednisolone during the interval time. Two weeks after the second session of pulse therapy with improvement of the lesions, during tapered dosage of oral prednisolone, facial annular erythematous lesions appeared and were superimposed by generalized pustular eruptions. Skin biopsy of pustular lesions showed pustular psoriasis so intramuscular methotrexate was added. Two years later, during decreasing dosage of methotrexate and prednisolone, she had eruptive recurrence of pustules and flaccid bullae associated with erythroderma and fever which were controlled with increasing dosage of corticosteroid and starting oral retinoid. These hypotheses may explain co-occurring pemphigus foliaceus and pustular psoriasis: decreasing dosage of corticosteroid, interleukin-8 overproduction in keratinocytes and increased activity of plasminogen activator in skin lesions.